Acquainted Strangers: Thwarted Interaction in Digitally Mediated Urban Gay Bars. (8th October 2020) - Baldor, Tyler
Abstract: While some situations in sexual contexts facilitate interaction, others can make overtures difficult to negotiate. Furthermore, social media creates new challenges as individuals navigate sexualized spaces in an increasingly digital world. Drawing on fieldwork in Philadelphia gay bars and supplemental interviews with young gay club-goers,  I find that men experience unexpected challenges that inhibit their ability to socialize with gay others and enact positive gay identities. I show how the social organization of particular bars, as well as the popularity of mobile dating applications, undermines the interactional accomplishment of positive outcomes such as identity affirmation and "having fun": (1) men's embodied work to evade effeminacy constrains their facial expressions, comportment, and speech; (2) gay bars' multiple functions as sexual fields and community outposts render both social and sexual interaction difficult to initiate; (3) patrons struggle over whether and how to interact with other mobile dating app users, a novel social tie I conceptualize as acquainted strangers, in the bars. I discuss how these mechanisms—managing stigma corporeally, negotiating discrepant frames, and navigating ambiguous social ties—may thwart interactional achievements while reproducing inequalities in contexts beyond the gay bar.